2003
DOI: 10.1063/1.1636818
|View full text |Cite
|
Sign up to set email alerts
|

Phototunable lasing in dye-doped cholesteric liquid crystals

Abstract: In this letter, we report the results of phototunable lasing in dye-doped cholesteric liquid crystals (DD–CLC). Photoexcitation of DD–CLC films gives rise to laser emission in the violet-UV range. Control of the structure of the chiral dopant driven by UV phototransformation is exploited in order to obtain a permanent variation of the cholesteric pitch. Laser emission wavelength tuning, by means of photoinduced shifting of the selective reflection band of the cholesteric liquid crystals is established. A tunin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 18 publications
1
78
0
1
Order By: Relevance
“…Control of the structure of the chiraldopant driven by UV photo transformation was exploited in order to obtain a permanent variation of the cholesteric pitch. Laser emission wavelength tuning was established with the help of photoinduced shifting of the selective reflection band of the cholesteric liquid crystals [32].…”
Section: Lasing In Dye Doped Cholesteric Liquid Crystalmentioning
confidence: 99%
“…Control of the structure of the chiraldopant driven by UV photo transformation was exploited in order to obtain a permanent variation of the cholesteric pitch. Laser emission wavelength tuning was established with the help of photoinduced shifting of the selective reflection band of the cholesteric liquid crystals [32].…”
Section: Lasing In Dye Doped Cholesteric Liquid Crystalmentioning
confidence: 99%
“…In first case to the nematic MLC-6816 was doped with a chiral compound ZLI-3786 whose chemical structure is identical to the one of ZLI-811. Like ZLI-811 the mixture NLC + ZLI-3786 undergoes a photo-Fries transformation [30,39] if irradiated at wavelengths shorter than 300 nm. To create a pitch gradient within the CLC layer containing ZLI-3786, distinct regions of the layer have been exposed to UV for different times using a customized mask.…”
Section: Dye Lasers With Clc Mirrorsmentioning
confidence: 99%
“…In [30] was proposed the tuning of the lasing wavelength by light. In this pioneering work the controlling of the generated laser wavelength was carried out by means of phototransformation of a well known chiral dopant from Merck ZLI-811 [left-handed (S-811) and righthanded ZLI-3786 (R-811)] whose light sensitivity was never considered before.…”
Section: Light Tunable Dddfb Clc Lasersmentioning
confidence: 99%
“…So far, reports have shown that low threshold laser action are readily observed not only in chiral nematic liquid crystal [4,5] but also in ferroelectric liquid crystal (smectic C Ã ) [6], blue phase liquid crystal [7], cholesteric polymer [8,9], cholesteric elastomer [10] and more recently cholesteric glasses [11]. Tunability of lasing in these systems can be achieved by the control of chiral agent concentration, external electrical field [12], temperature [13], mechanical stress [10], and photochemical effect [14,15].…”
Section: Introductionmentioning
confidence: 99%